Myeloablative therapy for primary resistant multiple myeloma - Alexanian, R.; Dimopoulos, M.A.; Delasalle, K.B.; Hester, J.; Champlin, R. (STEM CELLS, 1995)
Myeloablative therapy supported by autologous bone marrow or blood stem cell transplantation was assessed in 41 patients who had multiple myeloma resistant to vincristine‐doxorubicin by continuous infusion with high‐dose dexamethasone (VAD) or other high‐dose dexamethasone regimens. In patients who had high or intermediate tumor mass, the myeloma cell mass was reduced by more than 75% in 56% of patients and the survival time quadrupled in comparison with that of a matched control group. Later treatment resulted in a lower response rate and shorter remission. Current myeloablative regimens supported by autologous stem cells provided a useful treatment for patients who had advanced primary resistant multiple myeloma. Such treatment should be given early in the disease course to provide the best chance for remission, collecting blood stem cells with facility, and preventing complications that would increase the risk of the procedure. Copyright © 1995 AlphaMed Press
Keywords: Autologous marrow; Autologous stem cells; Early therapy; Late therapy; multiple myeloma; Myeloablative therapy; Primary resistance; Survival